Optimizing Employee Performance through an Effective Combination of Leadership, Work Ethic, and Work Discipline: A Study in the Contemporary Business Context - Safitri, Destia Risa Dwi; Muslih, Basthoumi (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: The current study tried to examine the effect of leadership, work ethic, and work discipline on employee performance at CV Putra Jaya - Nganjuk Regency. Design/Methode/Approach: This study employs a quantitative methodology incorporating causality techniques. The research is conducted at CV Putra Jaya, situated in Ketandan Village, Lengkong District, Nganjuk Regency. Total sampling is employed as the sampling technique, involving a comprehensive sample of 46 respondents. Data analysis is conducted using the multiple linear regression technique. Research Finding: Leadership, work ethic, and work discipline have a positive and significant influence on employee performance at CV Putra Jaya - Nganjuk Regency, partially and simultaneously. This indicates that if leadership at CV Putra Jaya going better, the employee performance will increase more. If the work ethic among CV Putra Jaya employees going better, higher employee performance will be achieved. Literally, increasing work discipline among CV Putra Jaya employees can improve their performance. Determination value of 43.7% indicates that employee performance can be influenced by these three independent variables. Theoretical contribution/Originality: - Practitioner/Policy implication: Leadership of the leader at CV Putra Jaya - Nganjuk Regency at a low effect level should be more flexible and authoritative. Research limitation: Current study variables only influenced employee performance by 43.7%, so other factors need to be studied further. Keywords: Leadership, Work Ethic, Work Discipline, Employee Performance.